ANALYSIS OF THERMAL DECOMPOSITION KINETICS AND THERMAL HAZARD ASSESSMENT OF NITROBENZOIC ACID ISOMERS BY DSC AND THERMOGRAVIMETRIC METHOD - Xin Yi Li; Zhi Xiang Xing; Ye Cheng Liu; Yang Cheng; An Chi Huang (Química Nova, 2025)
Nitroaromatic acids, ubiquitous intermediates in nitro compounds, find broad applications in pharmaceuticals and fine chemical industries, yet their safety often receives inadequate attention. This paper investigates the thermal decomposition process of three isomers of nitrobenzoic acid using differential scanning calorimetry (DSC) and thermogravimetric analysis (TG), complemented by calculations of the apparent activation energy using typical kinetic methods. The reaction type was verified using a nonlinear fitting method. Thermal safety parameters including the time to maximum rate (TMR), critical temperature of self-acceleration (TCL), and thermal risk index (TRI) were employed to elucidate the thermal hazards. The thermal decomposition mechanism was further explained using density functional theory (DFT) methods, focusing on the Mayer bond order. The findings revealed that the average apparent activation energies for p-nitrobenzoic acid (PNBA), m-nitrobenzoic acid (MNBA), and o-nitrobenzoic acid (ONBA) were 157.00, 203.43, and 131.31 kJ mol-1, respectively. A single n-order reaction characterized the thermal decomposition process. The TMR and TCL parameters indicated a decomposition tendency at high temperatures, with the thermal stability at elevated temperatures following the order: PNBA < ONBA < MNBA. The TRI parameter indicates the danger level of the nitrobenzoic acids. The thermal decomposition mechanism was elucidated using Mayer bond energies, offering valuable insights into storage and transportation, and contributing to developing predictive models for thermal characteristics.